Pan endulzado con panela (2015)
The Project, BREAD SWEETENED WITH PANELA, aims to conduct a feasibility study for the creation of a baking company, whose innovation is based on the transformation of the traditional formula of bread; achieving replace refined sugar for brown sugar as a natural sweetener. Through market research it seeks to analyze indicators such as demand and supply; and conduct technical studies to capture the needs required for the implementation of a company that meets quality standards and requirements necessary for assembly. Define the conditions that the organization should have to be competent in the market and implement business strategies that emphasize the virtues of the product and the location of the point of sale; also, organizational and legal studies which allowed design the structure and policies of the company, taking into account their respective regulatory requirements for forming the same. Make appropriate operational costs, financial test and profitability; which lists by facts, figures and values the viability of the project; and checking the implementation phase.